Perancangan Sistem Keamanan Central Lock Mobil Menggunakan Identifikasi E-KTP - Mega Putra Yogia Santoso (Politeknik Negeri Malang, 2019)
Currently, most motorized vehicle safety technologies, especially cars, still rely heavily on the manufacturer's default safety system from the car system itself. By using a security system from the factory default there are still shortcomings because a motorized vehicle or car can still be used by anyone and there is no age limit in its use. For that, we need a car safety system that is able to prevent the occurrence of car theft and underage drivers. The purpose of this research is to design a central lock security system for motor vehicles, especially cars, using e-KTP identification to improve the security system and reduce underage drivers. For the identification process of e-KTP ID using the RFID reader MFRC522. The RFID reader is connected to the Arduino Nano as a controller. The results of the research used the RFID reader to read e-KTP ID in a vertical and horizontal position with a distance of less than 12 mm. When there is an acrylic barrier and a glass barrier the maximum reading distance is less than 9 mm and the plate barrier cannot be read. The existence of obstacles makes reading the e-KTP card will be reduced.